KEPELOPORAN KAUM PEREMPUAN BERBASIS KEARIFAN LOKAL PERAN“KWT DEWI SRI” DALAM MENGELOLA KERAGAMAN DAN MEMBERDAYAKAN MASYARAKAT DI YOGYAKARTA - Mahmud Arif (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Local wisdom is recognized as a vital social capital in empowering society. This has showed by the achievement of KWT Dewi Sri in enlarging it’s public role through adaptive strategies. In a pluralistic society, with a poor of socio-economical condition after the earthquake, certainly it was a difficult for the women to empower theirselves, their families, and their society. But such unlucky conditions have been managed successfully by KWT Dewi, even they have stepped forward like the incarnation of Dewi Sri(Sri godless) that in Javanese mythology being convinced as a source of prosperity for farming of villagers, and gradually have succeeded in refuting a view of feminization of poverty.